A three-dimensional quasicontinuum approach for predicting biomechanical properties of malaria-infected red blood cell membrane - Adesola Ademiloye (Applied Mathematical Modelling, 2017)
This paper presents the first attempt to comprehensively estimate the elastic properties and mechanical responses of malaria-infected red blood cell (iRBC) membrane when subjected to uniaxial, shear and isotropic area-dilation loading conditions. With the three-dimensional (3D) quasicontinuum approach, we predicted the biomechanical properties of the iRBC membrane for all infection stages. Effect of temperature on the membrane elastic properties during the trophozoite stage was also examined. It is found that a multifold increase in the elastic properties of the iRBC membrane occurs as infection progresses. The axial, shear and area stiffnesses of the iRBC membrane increase exponentially, resulting in semi-logarithmic stress–strain relationship curves. In addition, the rigidity of the iRBC membrane in the trophozoite stage increases as temperature rise. It is concluded that Plasmodium falciparum parasites significantly affect the biomechanical properties of the RBC membrane due to the structural remodeling of the iRBC membrane microstructure.